2000
DOI: 10.1038/sj.bjp.0703690
|View full text |Cite
|
Sign up to set email alerts
|

Differential vasoconstrictor activity of human urotensin‐II in vascular tissue isolated from the rat, mouse, dog, pig, marmoset and cynomolgus monkey

Abstract: 1 Urotensin-II (U-II) and its G-protein-coupled receptor, GPR14, are expressed within mammalian cardiac and peripheral vascular tissue and, as such, may regulate mammalian cardiovascular function. The present study details the vasoconstrictor pro®le of this cyclic undecapeptide in di erent vascular tissues isolated from a diverse range of mammalian species (rats, mice, dogs, pigs, marmosets and cynomolgus monkeys). 2 The vasoconstrictor activity of human U-II was dependent upon the anatomical origin of the ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
177
1
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(188 citation statements)
references
References 40 publications
6
177
1
4
Order By: Relevance
“…Expression of U-II and UT receptor has been reported in kidney, CNS, and in the cardiovascular system (10 -14). Pharmacological studies have shown that U-II exerts potent vasoactive activity in different mammal species, including humans and rats (13,(15)(16)(17)(18)(19). The contractile activity of U-II is mediated by the activation the small GTPase RhoA and its effector, Rho kinase (20).…”
mentioning
confidence: 99%
“…Expression of U-II and UT receptor has been reported in kidney, CNS, and in the cardiovascular system (10 -14). Pharmacological studies have shown that U-II exerts potent vasoactive activity in different mammal species, including humans and rats (13,(15)(16)(17)(18)(19). The contractile activity of U-II is mediated by the activation the small GTPase RhoA and its effector, Rho kinase (20).…”
mentioning
confidence: 99%
“…It has been shown that UII is an endogenous ligand for the orphan G protein-coupled receptor GRP14 (5), which is now termed as urotensin II receptor (UT-R) (6). UII has been demonstrated to exert a profound vascular effect including vasoconstrictor activity (5,7,8) and vasodilator activity (9,10) dependent on the anatomic sites and the species studied. In addition, UII has a positive inotropic effect (11) and stimulates the proliferation of vascular smooth muscle cells (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Ames et al (1999) described potent vasoconstrictor activity of human U-II in arterial, but not venous, preparations from a wide range of vascular territories in cynomolgus monkeys, whereas the vasoconstrictor activity, in preparations from rats, was restricted to the thoracic aorta. Marked species dierences, and regional variations in the vasoconstrictor eects of human U-II, have since been shown by others (Bottrill et al, 2000;Douglas et al, 2000;Maclean et al, 2000;Maguire et al, 2000). Vascular contractions induced by human U-II are described as being slow in onset, sustained and resistant to washout, and the potency of human U-II to cause constriction is generally found to be either greater than, or equal to, that of endothelin.…”
mentioning
confidence: 99%
“…Douglas et al (2000) alluded to unpublished observations showing the lack of systemic pressor responses to human U-II in anaesthetized or pithed rats, but clearly, as stated by Bottrill et al (2000), the marked regional variations in the vascular responses to U-II make it dicult to interpret data restricted to measurements of blood pressure. Therefore, the aim of the present study was to establish the regional haemodynamic eects of human U-II in conscious, freely-moving rats.…”
mentioning
confidence: 99%